If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 3(2 + 1) = -22 + 4(3z + -5) Combine like terms: 2 + 1 = 3 4z + 3(3) = -22 + 4(3z + -5) Multiply 3 * 3 4z + 9 = -22 + 4(3z + -5) Reorder the terms: 9 + 4z = -22 + 4(3z + -5) Reorder the terms: 9 + 4z = -22 + 4(-5 + 3z) 9 + 4z = -22 + (-5 * 4 + 3z * 4) 9 + 4z = -22 + (-20 + 12z) Combine like terms: -22 + -20 = -42 9 + 4z = -42 + 12z Solving 9 + 4z = -42 + 12z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12z' to each side of the equation. 9 + 4z + -12z = -42 + 12z + -12z Combine like terms: 4z + -12z = -8z 9 + -8z = -42 + 12z + -12z Combine like terms: 12z + -12z = 0 9 + -8z = -42 + 0 9 + -8z = -42 Add '-9' to each side of the equation. 9 + -9 + -8z = -42 + -9 Combine like terms: 9 + -9 = 0 0 + -8z = -42 + -9 -8z = -42 + -9 Combine like terms: -42 + -9 = -51 -8z = -51 Divide each side by '-8'. z = 6.375 Simplifying z = 6.375
| 5m^2-8m=0 | | 7-2(x)-2(-10)=15 | | -9(-x+2)+10=-35 | | -30.5=-3(7.5f+5.5) | | 1/2(x-1)-(x-3) | | 9x-5(x+6)=10 | | 2y+1x=10 | | 49+99= | | x+(x+1)=500 | | 2+(5a)=16 | | -2g=4(4+g)+2g-4(6-3g) | | 3/8(4p+6)=1/2p-17 | | -6.5v-7+5v=-27.5 | | 9x-5(x-6)=10 | | 3x+2=-2xn-8 | | n-19=48 | | (y*2)+15=55 | | -2/5(45) | | x+0.75=14 | | 55=15+(y*2) | | 8-12-(-6)= | | x^2-21x+25=0 | | 7+4(1-6.5s)=21.5 | | (y*2)+15= | | 7s-25=-23+8s | | 4r-6=9+r | | 6.5x+20=(10+x)(4) | | n-4=43 | | 3b-2(b-5)=2(b+4) | | 280=53l | | (55-15)/2= | | 9x+4=8x+14 |